Development of an Efficient Synthetic Process for Irisquinone - Zheng, Kun; Zhang, Qifeng; Ma, Yuheng; Liang, Guodong; Zhao, Yan; Ga, Lu (Synlett, 2024)
Irisquinone is a tumor radiotherapy sensitizer and has been found to have broad-spectrum antitumor activity in recent years. The current acquisition method of extracting and purifying from semen irisis has greatly limited its wide application and activity study deeply. In this work an efficient route for the synthesis of the irisquinone was investigated to solve the source of it. The target compound was synthesized by 5-step reactions to Wittig reaction, reduction, oxidation, Wittig reaction, and oxidation using 3,5-dimethoxycarboxaldehyde as the starting material with an overall yield of 48%. The key factors such as the ratio of raw materials, temperatures, solvents, reaction times, and types of base for the main reactions were optimized. In addition, the deprotection and reduction were completed with Pd/C catalytic simultaneously when compound 2 was synthesized from compound 1. In the last reaction, the 3,5-dimethoxybenzene moiety of compound 4 was directly oxidized to 6-methoxy-1,4-benzoquinone by K3[Fe(CN)6]/H2O2 without the need to selectively remove the methyl protecting group, which were the innovative points in the experimental route design of the irisquinone synthesis. This work has opened new perspectives for the artificial synthesis and the development of irisquinone.
Keywords: irisquinone; semen irisis; radiotherapy sensitizer; synthetic process; antitumor agents; Irisquinone